Experiences of School Counseling Trainees in a Primary Care Integrated Behavioral Health Care Practicum - Kaprea Johnson; Krystal Clemons; Lauren Robins; Alexandra Gantt-Howrey; Afroze Shaikh; Heather A Jones (Teaching and Supervision in Counseling, 2023)
Youth integrated behavioral healthcare (IBH) is a preferred method of service delivery, and school system expertise on these teams is imperative. In this descriptive phenomenological study, we sought to understand the experiences of five school counseling practicum students (SCITs) engaged in IBH in an urban children's hospital. Phenomenological analysis resulted in five themes: (a) contributing school system knowledge, (b) expansion of professional identity through practical application, (c) collaborative interventions and techniques, (d) interprofessional supervision, and (e) program and setting challenges. Implications for counselor education and supervision, including IBH-specific training for SCITs, conclude.
Keywords: School counseling practicum students; integrated behavioral health care; interprofessional collaboration; professional identity; phenomenology